The Effect of Green Intellectual Capital, Green Accounting and Company Size on the Financial Performance of Food and Beverage Sector Industry Listed on IDX for the Period 2020-2023 - Lutfi Eka Sabita; Sunita Dasman (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to analyze the influence of green intellectual capital, green accounting and company size on the financial performance of the food and beverage industry during the 2020-2023 period. As awareness of the importance of sustainability increases, companies in this industry need to integrate environmentally friendly practices into their operations. The research employs a quantitative analysis method, utilizing data from the food and beverage industry companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, comprising a total of 18 samples. The sampling technique applied is purposive sampling, and the analysis is conducted using EViews version 12. So this research shows that green Intellectual Capital and Green Accounting have a significant positive influence on financial performance, while company size also helps improve financial performance. It is hoped that these findings will provide insight for company management to implement sustainable strategies to improve financial performance.